Students Perception towards English Online Classroom Via Zoom During the Covid-19 Pandemic - Shanty Halim (Institut Agama Islam Negeri Palopo, 2022)
This study aimed at determining the perceptions of English Language Education students of Politeknik Negeri Ujung Pandang on English Learning class via Zoom during the Covid-19 pandemic. The qualitative descriptive method was carried out by distributing questionnaires using Google Form to 45 English online classrooms students at Politeknik Negeri Ujung Pandang after completing the learning process for 3 months. The results of this study show that (1) the use of Zoom application provides new experiences in online learning activities, (2) students can easily operate some of the Zoom application features, (3) the learning process expects students to use the Zoom application, (4) the Zoom application is one of the e-learning tools that can support online learning activities continuously, (5) the use of Zoom application because the classmates agree to use the Zoom application, and (6) students can use the Zoom application easily in carrying out of online learning activities.